Challenges and Solutions in the Implementation of English-Based Job-Sheets for Engineering: Voices from Vocational Schools - Rizky, Ramanda; Maulana, Fajar; Ustafiano, Bintha; Yunefri, Yogi (Journal of Vocational Education Studies, 2025)
Jobsheet is a set of documents that contain instructions or guidelines for carrying out a specific task or job, usually in the context of education or training. Therefore, this study explores the implementation of English for Engineering (EFE)-based Jobsheets in the Light Vehicle Engineering Expertise Program at SMK Muhammadiyah 1 Pekanbaru. Aditionally, using a descriptive qualitative approach, this study involved 38 students and several teachers who are directly involved with EFE Jobsheets. Data were collected through interviews, observations, and document analysis. At the same time, it was found that the EFE Jobsheets had a positive impact on students' understanding and application of technical English, improving their competencies in terms of both technical and language skills. However, challenges such as students' weak English foundation, inadequate teacher competence, and limited resources were identified. Solutions to these issues include continuous teacher training, development of interactive materials, and collaboration with industry to offer practical experience. In spite of the promising results of the EFE-based Jobsheet implementation, continuous improvements in developing multimedia-based interactive materials and industrial simulations are essential to optimize learning outcomes.